Delphi Survey of Clinical Nursing and Midwifery Research Priorities in the Eastern Mediterranean Region. Issue 2 (8th February 2017) - Sun, Carolyn; Dohrn, Jennifer; Oweis, Arwa; Huijer, Huda Abu‐Saad; Abu‐Moghli, Fathieh; Dawani, Hania; Ghazi, Cheherezade; Larson, Elaine
Abstract: Purpose: As the shortage of nurses and midwives is expected to worsen in the Eastern Mediterranean region concomitantly with a growing focus on achievement of universal health coverage, nurses and midwives are expected to fill major gaps in health care. Hence, the need for a solid evidence base for nursing practice and a clear direction for clinical nursing research are paramount. Therefore, a Delphi survey was conducted to determine clinical (research focused on patient outcomes) nursing and midwifery priorities for research within this region. Design: A Delphi survey, using iterative rounds of an online survey of regional clinical nursing and midwifery research experts, was conducted between January and April 2016. Methods: Consensus was determined by percentage agreement on level of priority for topics as determined by participants. Additionally, results were compared between countries within the region by income and mortality levels using Kendall's tau. Findings: Critical research topics were focused on public/community/primary care as well as emergency preparedness for disasters, and these priorities are well aligned with gaps in the literature for this region. There were statistically significant differences between priority level and country mortality group for geriatrics, self‐management of disease, and sexually transmitted infections. Conclusions: Critical research priorities should focus on population‐based health topics. Between‐country differences should be analyzed further. A clinical research database for the region may help improve research access for nurses and midwives. Clinical Relevance: Practicing nurses and midwives lack extensive evidence (including culturally relevant evidence) on which to practice. Increasing research in areas identified in this survey may improve patient outcomes and quality of care regionally.